Evaluasi Water Sustainability Index Pada Sistem Penyediaan Air Bersih Berbasis Masyarakat di Mata Air Lerak, Kota Semarang - Pramesti, Angelina Cahya; Fariz, Trida Ridho (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
The need for water continues to rise with population growth, while environmental degradation threatens its availability. In Semarang City, nearly half of the springs show declining discharge. Lerak Spring, still used directly by the community, faces pressure from settlement expansion and weak management. This study aimed to evaluate the sustainability of the community-based clean water supply system at Lerak Spring using the Water Sustainability Index (WSI) within the Sustainability Assessment Framework for Community Water Systems (SAFE-Comm). Data were collected through observation, interviews, and documentation combined with indicator scoring. The results show a score of 2.59, categorized as good, indicating that the system meets community needs to a degree but still requires further improvement.